2019
DOI: 10.1155/2019/2081027
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Spherical Cellulose Nanoparticles from Ionic Liquid Processing via Novel Nonsolvent Addition and Drying

Abstract: A novel method to prepare spherical cellulose nanoparticles has been developed using imidazolium ionic liquid processing and regeneration from controlled acetonitrile nonsolvent addition and drying. Nanoparticles ranging from 100 to 400 nm have been prepared with high uniformity. Minimisation of moisture via solvent exchange drying led to discrete nanoparticles, whereas the presence of ambient moisture during regeneration contributed to aggregated morphologies. Chemical analyses of the spherical cellulose nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
(18 reference statements)
1
16
0
Order By: Relevance
“…SEM images of cellulose regenerated with acetonitrile (a, b) cellulose regenerated with water (c, d) . Copyright 2019 Hindawi.…”
Section: Ils-assisted Processing Of Bioresources For Nanocellulose Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…SEM images of cellulose regenerated with acetonitrile (a, b) cellulose regenerated with water (c, d) . Copyright 2019 Hindawi.…”
Section: Ils-assisted Processing Of Bioresources For Nanocellulose Pr...mentioning
confidence: 99%
“…Recently, Hakkak and co-workers 84 regenerated spherical cellulose nanoparticles from MCC using [Emim][OAc] where acetonitrile and water were used as nonsolvents. First, cellulose in [Emim][OAc] solution was prepared under the nitrogen atmosphere at 80 °C for 16 h. For the regeneration, acetonitrile was added to the solution and subsequently washed with acetone four times and diethyl ether three times.…”
mentioning
confidence: 99%
“…In the domain of sphere-shaped cellulose-based nanoparticles, nanoprecipitation [ 94 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ], and emulsification processes [ 167 , 168 , 169 , 170 , 171 , 172 , 173 ] are the most used production methodologies, although other less common approaches, namely mechanical treatments [ 174 , 175 , 176 , 177 ], chemical and/or enzymatic treatments [ 178 , 179 , 180 , 181 , 182 ], and layer-by-layer assembly [ 183 ], can also be used to assemble nanospheres [ 179 , 181 , 182 ] and nanocapsules [ 159 , 168 , 169 , 183 ]. Regarding the cellulosic substrate, most of the studies, as in the case of cellulose-based microparticles, report the use of cellulose derivatives, such as CA [ 184 ], CMC [ 159 , 168 , 183 ] and EC [ 141 , 161 , 169 , 170 , 171 , 172 , 173 , 185 ], although some examples of native cellulo...…”
Section: Production Of Spherical Cellulose-based Nanoparticlesmentioning
confidence: 99%
“…The nanoprecipitation method has also been applied using pure cellulose dissolved in alternative solvents, such as ILs [ 165 ]. Regarding the parameters that influence this process, the H-bond acidity of the antisolvent has been shown to affect the regeneration of pure cellulose from ILs.…”
Section: Production Of Spherical Cellulose-based Nanoparticlesmentioning
confidence: 99%
“…Generating the uniform spherical nanoparticles is problematic through chemical, ionic liquid, or mechanical approaches. Hakkak et al [97] reported a novel facile method for creating and isolating spherical cellulose nanoparticles from the ionic liquid using acetonitrile nonsolvent addition. This novel method of regenerating the spherical nanoparticles is a simple procedure which produces the spherical cellulose nanoparticles of the size range 100-400 nm with high uniformity.…”
Section: Spherical Cellulose Nanoparticlesmentioning
confidence: 99%